Model Trinitarian Sebagai Pendekatan Alternatif Terhadap Disabilitas - Harisantoso, Imanuel Teguh (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2024)
This research aims to explore alternative models of disability. The charity, medical, social, rights-based and cultural models of disability have had a tendency to bring disability into aperichoreticd stigmatizing categorization. The “model” approach to disability, which originally acted as a means of liberation, instead isolates disability in the category of people who are weak, sick, have no potential, have no rights and therefore deserve the identity of sinners. Disability as a social construct is the result of the strong hegemony of eugenics that upholds normality. Postcolonial approaches aid resistance to colonialism and colonialist ideologies that emerge in new forms. The dominance of normality ideology places disability against abnormality, including domination and marginalization of disability. The perspective of normality against abnormality, non-disability against disability shows a negative relationship between two human entities. For this reason, an alternative model is needed, a relationship whose existence is actually emphasized by the other. One does not exist without the other. I exist because you exist. This relationship is only possible if the existing relationship is a reflection of the trinitarian relationship, where the perichoretic relationship between God the Father, God the Son, and God the Holy Spirit becomes the basis for understanding human relations between both disabilities and non-disabilities.